INSTALASI DAN KONFIGURASI JARINGAN VSAT MENGGUNAKAN MODEM GILAT PADA PT. INDO PRATAMA TELEGLOBAL JAKARTA - Germanus Yosef Rugi Laka; Luci Kanti Rahayu; Yahdi Kusnadi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
PT. Indo Teleglobal is one vendor that specializes in infrastructure and internet service providers. Customer or Client in Sorong and Jayapura need internet service to send data or information to the central office in Jakarta where they are constrained by geographical conditions and do not allow for the use of optic fiber (FO). Overcoming the problems it is given the service of Very Small Aperture Terminal (VSAT). In addition to sending data or browsing, VSAT is also used to communicate with headquarters in Jakarta by using voice over Internet Protocol (VOIP) that the system connections through satellites. Compared with a terrestrial data communications network, data communication network via satellite has many advantages, among them capable of handling a wide area communications network. The author uses research methods that include requirements analysis, design, testing, and implementation.